Edukasi Senam Hamil Pada ibu Hamil Trimester III Sebagai Persiapan Persalinan di Desa Oben Kecamatan Nekamese Kabupaten Kupang - Pratiwi, Endah Dwi; Ahmad, Siti Nur Asyah Jamillah; Jumetan, Mili Arthanedi (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Pregnancy exercise is a fitness program intended for pregnant women. Pregnancy exercise aims to prepare and train the muscles so that they are used to function optimally in normal childbirth. Implementation of pregnancy exercises carried out by pregnant women in the third trimester can reduce discomfort in complaints of swelling in the legs, back pain, lower back pain, leg cramps and difficulty sleeping. The results of the study show that there is an influence of pregnancy exercises on the discomfort of low back pain, back pain, swelling in the legs and cramps. on the feet. This socialization and training activity on pregnancy exercise was carried out on January 17 2024 in Oben Village, Nekamese District, Kupang Regency, involving lecturers and program holders at the local health center as well as cadres. The participants who took part in this activity were 7 third trimester pregnant women and 3 lecturers as well as 1 program holder midwife and 3 cadres. It is known that the implementation of this community service activity ran smoothly. The results of this activity also show that there has been an increase in information and ability to apply pregnancy exercises. Apart from that, pregnant women also stated that they understood pregnancy exercise and the benefits of facing childbirth.